Detection of Formalin Content And Quality Properties of Snakehead (Channa striata) Dried Salted Fish From The Traditional Markets In Pontianak City In Indonesia - Eva Mayasari; Muhammad Azlan; Tri Rahayuni (Universitas PGRI Semarang, 2019)
The snakehead fish (Channa striata) dried salted fish is one of the freshwater salted fish favored by local people in Pontianak city, West Kalimantan, Indonesia. The aim of this research was to identify the formalin content and status of the quality properties of the Snakehead dried salted fish in the traditional markets in Pontianak city. Sampling is carried out in five traditional market selected i.e. Mawar, Dahlia, Puring, Kenanga dan Flamboyan. The determination of formalin was carried out by qualitative and quantitative methods using the Schiff reagent. All the samples are appropriate with SNI standard in salt content ranged from 7,08-8,49% and water content ranged from 36,66 – 39,04%. The level of panelists acceptance for appearance score ranged from 6,70–7,06 (whole, clean, slight dullness), the odor score ranged from 6,26 – 6,93 (neutral, slight odor additive - slight natural odor, slight odor additive), and the texture score ranged from 6,48 – 7,36 (solid, some loss of elasticity-very firm, some loss of elasticity). All the samples are contained formalin ranged from 0,64-0,83 ppm. The total plate count (TPC) of the samples was found ranged from 2,1 x 107 - 7,0 x 107 Cfu/g.